A quantitative analysis of total carbohydrate content from the salivary expectorants in young children - Snehalika Ashok More; Sandya S Patil; Madhu Kakanur; Rachna Thakur; Mihir N Nayak; S Ravi Kumar (Wolters Kluwer Medknow Publications, 2018)
Background: In this postfluoride era, the concentration of fermentable carbohydrate in saliva after food intake is important to determine the risk of developing dental caries. Aim: The aim of this study is to estimate the total carbohydrate content of salivary expectorants following consumption of commercially processed snacks. Design: Thirty children aged 6-8 years were selected for estimation of total carbohydrate content of salivary expectorants using modified calorimetric anthrone-sulfuric acid-glucose reaction. The test foods analyzed were as follows: Test food A - potato chips, Test food B - glucose biscuits, Test food C - Oreo biscuits, Test food D - cake, and Test food E - cornflakes. The data obtained were analyzed using student's t-test and ANOVA. Results: The difference between the mean carbohydrate values of salivary expectorants of various processed test food groups at 0 and 10 min was statistically significant (P ≤ 0.001). After 10 min interval, cornflakes were found to have highest total carbohydrate content in salivary expectorant (5.186 mg/ml). Conclusion: The foods with high starch content such as cornflakes and potato chips exhibited higher total carbohydrate content, thus depicting lower salivary clearance rate.